Analyzing The Main Drivers of Observed PM2.5 Concentrations in South Korea during the 1st to 5th Seasonal Particulate Matter Management Periods 1~5차 미세먼지 계절관리제 기간 국내 초미세먼지 관측 농도 변화 요인 분석 - Kang, Yoon Hee; Kim, Eunhye; Jung, Sungeun; Park, Junheung; Son, Chaewon; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2024)
To analyze the causes of the observed reduction in PM2.5 concentrations in South Korea during the 1st to 5th Seasonal PM Management periods (S1~S5), observational data and air quality modeling were utilized, including data from the same periods over the previous three years (BS3~BS1; BS). Observed PM2.5 concentrations during S1~S5 decreased by 8.2 μg/m3 compared to the BS periods, while emission impacts reduced PM2.5 concentrations by 9.5 μg/m3, and the influence of meteorological conditions increased PM2.5 concentrations by 1.3 μg/m3. Although meteorological conditions changed to reduce PM2.5 concentrations during the 5th Seasonal PM Management period, both long-term and short-term meteorological conditions could potentially increase PM pollution again. During the same periods, the impacts of long-range transport (LTI) and local emissions (LEI) decreased by 5.8 μg/m3 and 2.4 μg/m3, respectively. Overall, the recent trend of reducing LTI due to reductions in upwind foreign emissions has contributed to lower PM2.5 concentrations in South Korea during the S1~S5 periods. However, the rate of improvement in PM2.5 concentrations in upwind areas such as China is expected to slow down. Therefore, more proactive domestic emission control measures and policies are necessary to further improve PM2.5 levels in South Korea. This study employed foreign emissions adjustment, considering the uncertainty and severe spatial variability of domestic emissions. To develop advanced domestic emission management and effective strategies, it is essential to establish an emission estimation method that accurately reflects the current state of PM2.5 concentrations.
Keywords: Emissions adjustment; LTI and LEI; Meteorology and emission conditions; PM2.5; Seasonal particulate matter management periods